2006 annual report : (PPIAF, 2006)
Contents of the book include: Framing infrastructure development strategies to take full advantage of the potential for private involvement; building consensus on appropriate policy, regulatory, and institutional reforms; designing and implementing spacific policy, regulatory and institutional reforms.